ERβ Accelerates Diabetic Wound Healing by Ameliorating Hyperglycemia-Induced Persistent Oxidative Stress - Zhou, Xueqing; Li, Min; Xiao, Meifang; Ruan, Qiongfang; Chu, Zhigang; Ye, Ziqing; Zhong, Liyan; Zhang, Haimou; Huang, Xiaodong; Xie, Weiguo; Li, Ling; Yao, Paul (Frontiers in Endocrinology, 2019)
Delayed wound healing in diabetic patients is a serious diabetic complication, resulting in major health problems as well as high mortality and disability. The detailed mechanism still needs to be fully understood. In this study, we aim to investigate potential mechanisms and explore an efficient strategy for clinical treatment of diabetic wound healing. Human umbilical endothelial cells were exposed to hyperglycemia for 4 days, then switched to normoglycemia for an additional 4 days. The cells were harvested for the analysis of reactive oxygen species (ROS) generation, gene expression and VEGF signaling pathway. Furthermore, the diabetic wound model was established in rats for the evaluation of wound healing rates under the treatment of either ERβ agonist/antagonist or SOD mimetic MnTBAP. Our results show that transient hyperglycemia exposure results in persistent ROS overgeneration after the switch to normoglycemia, along with suppressed expression of ERβ, SOD2 and the VEGF signaling pathway. Either ERβ expression or activation diminishes ROS generation. In vivo experiments with diabetic rats show that ERβ activation or SOD mimetic MnTBAP diminishes ROS generation in tissues and accelerates diabetic wound healing. Transient hyperglycemia exposure induces ROS generation and suppresses ERβ expression, subsequently resulting in SOD2 suppression with additional elevated ROS generation. This forms a positive-feed forward loop for ROS generation with persistent oxidative stress. ERβ expression or activation breaks this loop and ameliorates this effect, thereby accelerating diabetic wound healing. We conclude that ERβ accelerates diabetic wound healing by ameliorating hyperglycemia-induced persistent oxidative stress. This provides a new strategy for clinical treatment of diabetic wound healing based on ERβ activation.